Deteksi Dini Anemia Berdasarkan Tanda Gejala dan Pemeriksaan Hb pada Remaja Putri di SMPN 18 Palembang - Bella Regita Az-Zahra; Intan kumalasari; Maliha Amin (Pusat Riset dan Inovasi Nasional, 2025)
Background: Anemia is one of the public health problems commonly found among adolescent girls, especially in developing countries like Indonesia. This condition affects concentration, academic performance, and productivity, making early detection an essential step to prevent long-term complications. Objective: This study aims to determine the results of early detection of anemia based on clinical symptoms and hemoglobin (Hb) levels among adolescent girls at SMPN 18 Palembang. Methods: This research used a descriptive design with a cross-sectional approach. A total of 132 seventh-grade female students were selected randomly. Data were collected through an anemia symptom questionnaire and hemoglobin level measurement using a hemoglobinometer. Results: The study found that 23.5% of respondents were anemic (Hb < 12 g/dL), and 48.5% showed symptoms of anemia. However, the sensitivity of symptoms in detecting anemia was only 39%, specificity was 19%, with a positive predictive value (PPV) of 60.93% and a negative predictive value (NPV) of 8.82%. Conclusion: Based on the findings, symptom-based detection alone is not sufficiently accurate to diagnose anemia. Hemoglobin level examination is still required as a more valid and objective screening method for the early detection of anemia in adolescent girls In addition to medical intervention, the study advocates for increased awareness and education about anemia, its causes, and prevention methods among students, parents, and educators. Addressing nutritional deficiencies, especially iron intake, through dietary improvements and supplementation is essential in combating anemia in adolescent girls.